Towards a Flexible and Sustainable Housing Enabling Approach in Iraq - Faris Dhumad Al-Essawi, K (KnE Engineering, 2018)
The research problem has emerged in light of the weakness of housing enabling measures in Iraq, and the lack of clarity of its formulas and levels. The aim of this research is to define objective frameworks that contain flexible formulas for the possible levels of housing enabling in light of the current situation and its future expectations. This has led to a hypothesis: housing enabling, as a method, will be efficient if put on the principles of flexibility and sustainability that ensure consistency and objectivity. Concepts of housing enabling were reviewed, the study concluded that: enabling is a philosophy and vision, translated into a method and a strategy; the vision is that the provision of housing is a participatory necessity, and the method is that enabling is a part of the housing process, with constituents, practical mechanisms and operational alternatives. Accordingly, the research proposed a formula for an enabling method with six constituents and some procedural mechanisms, as well as four alternatives of the types of housing projects to implement. This empirical model formula was applied in practice to the National Housing Policy in Iraq 2010, showing that the practical procedures of the national policy were very close to the constituents and the operational alternatives of the proposed method except for some partial details of the mechanisms, in addition one of the operational alternative is not covered that is type of developing housing projects. Finally, the research recommends reviewing housing enabling measures in the light of a comprehensive housing strategy.